Sonographic Assessment of Portal Vein Diameter among Healthy Adults in Saudi Arabia - Salah Albagir; Babiker A. Wahab; Ahmed Abdulrahman; Mogahid M.A. Zidan; Mohammed Yousef; Mustafa Z. Mahmoud; Ala M. A. Elgyoum; Mohamed Adam (International Journal of Biomedicine, 2020)
Background: The purpose of this study was to evaluate the mean values of the portal vein diameter (PVD) and establish its ultrasound reference values in healthy Saudi adults. Methods and Results: A total of 124 healthy adult volunteers (45.2% males and 54.8% females, a mean age of 44.8±16 years), presenting at the US Department of El-Karama Medical Center in Riyadh, Saudi Arabia, were recruited between November 2018 and May 2019 for this prospective study. Abdominal US scans were conducted on a Hitachi Aloka F37 machine with a curvilinear transducer with a frequency of 3.5MHz. The data collection sheets completed for each subject included the following variables: sex, age, height, weight, and BMI (kg/m2). The mean PVD was 10.40±1.22mm and higher in men (10.7±1.1mm) than in women (10.1±1.2mm) (P<0.05). Study results showed that PVD did not correlate with age and BMI. Conclusion: Further large-scale studies are needed to establish ultrasound reference values for PVD in healthy Saudi adults.